The place of racism: a discussion on O fascismo da cor by Muniz Sodré - Suiama, Sergio Gardenghi (Argumentum, 2026)
This article critically discusses Muniz Sodré’s book O fascismo da cor, in which racism in Brazil is conceptualised as a social rather than a structural form. By engaging with authors who approach the issue from a sociological perspective, the article argues that interpretations recognizing race as a key factor in shaping positions within the system of social stratification should not be disregarded.